Ultralow loading palladium nanocatalysts prepared by atomic layer deposition on three-dimensional graphite-coated nickel foam to enhance the ethanol electro-oxidation reaction. Issue 16 (2nd February 2016) - Jiang, Yiwu; Chen, Jinwei; Zhang, Jie; Li, Anqi; Zeng, Yaping; Zhou, Feilong; Wang, Gang; Wang, Ruilin
Abstract : Ultralow loading palladium nanoparticles were facilely synthesized on a three-dimensional graphite-coated nickel foam support by metal atomic layer deposition technology and used as a promising catalyst for ethanol electro-oxidation reaction. Abstract : A novel three-dimensional graphite-coated nickel foam (GNF) was synthesized by the chemical vapor deposition (CVD) method, and palladium nanoparticles (Pd NPs) were successfully synthesized on a GNF support by metal atomic layer deposition (ALD) technology for the first time. The physicochemical properties of the as-prepared catalysts were characterized by X-ray diffraction (XRD), Raman spectroscopy, scanning electron microscopy (SEM), energy dispersive X-ray spectrometry (EDS), X-ray photoelectron spectroscopy (XPS) and inductively coupled plasma-atomic emission spectrometry (ICP). Results showed that the Pd NPs with ultralow loading (below 50 μg cmPd −2 ) were uniformly dispersed on the GNF support, and the as-prepared catalysts presented the highest catalytic activity toward ethanol electro-oxidation (the peaking current density was about 39.97 mA cm −2 ) in alkaline media. In particular, it was found that the morphology and content of graphite of the GNF will greatly affect the dispersion of the ALD Pd NPs. When the CVD time for preparing the GNF was 10 min, the as-prepared catalyst presented a higher dispersity of Pd NPs and catalytic activity toward ethanol electro-oxidation than that of other as-prepared catalysts. The effect of the ALD cycle for Pd NPs growth and its performance was also investigated. When the cycle of ALD Pd was 450, the peaking current density of the as-prepared catalysts was about 2.64 times as high as that of commercial Pd/C to ethanol electro-oxidation. Herein, there is a promising application prospect for the prepared Pd/GNF nanocomposite as an electrocatalyst toward ethanol electro-oxidation in alkaline media.